The effect of student’s emotional intelligence on self-leadership in Malaysian public university - Amzat, Ismail Hussein; Thabit Al-Ani, Wajeha; Abubakar Yusuf, Habibat (IIUM Press, International Islamic University Malaysia, 2018)
This study aims to investigate using quantitative approach the effect of student’s emotional intelligence on self-leadership among Malaysian and international students in Malaysian public university. It also strives to examine whether student nationality plays a significant moderating role between emotional intelligence and self-leadership with 171 local and international students surveyed. Structural Equation Model through SmartPLS was used to know the effect and moderation. Findings of this study reported the direct-effect of student EQ on self-leadership and found significant moderation effect of student nationality between EQ (self-management) on self-leadership. The findings of this study were discussed and some suggestions, recommendations and implications were made for future studies’ investigations and practices. © 2018, International Islamic University Malaysia. All rights reserved.